Obstructive Sleep Apnea and Driving: A Canadian Thoracic Society and Canadian Sleep Society Position Paper - Najib Ayas; Robert Skomro; Adam Blackman; Kristen Curren; Michael Fitzpatrick; John Fleetham; Charles George; Tom Hakemi; Patrick Hanly; Christopher Li; Debra Morrison; Frédéric Series (Canadian Respiratory Journal)
Individuals with obstructive sleep apnea (OSA) experience sleep fragmentation and poor sleep quality that results in daytime sleepiness, which impairs performance during driving and leads to an increased risk for collisions. Not surprisingly, observational studies have shown that patients with OSA experience a two- to 10-fold higher risk for collision compared with healthy controls. Although treatment would clearly mitigate these risks, there is no current Canadian position on driving and OSA. This article, the first Canadian position statement addressing the issue, provides an overview of provincial regulations and proposes recommendations with regard to driving in patients with OSA.